2021
DOI: 10.1016/j.jamda.2020.07.020
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of the Sub-Acute Care for Frail Elderly (SAFE) Unit on Hospital Readmission, Emergency Department Visits and Continuity of Post-Discharge Care

Abstract: Objectives: In Canada, alternate-level-of-care (ALC) beds in hospitals may be used when patients who do not require the intensity of services provided in an acute care setting are waiting to be discharged to a more appropriate care setting. However, when there is a lack of care options for patients waiting to be discharged, it contributes to prolonged hospital stays and bottlenecks in the health care system manifested as "hallway medicine." We examined the effectiveness of a function-focused transitional care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…[ 10 31 ] Another study found the odds of readmission reduced by 56% when discharge plans were sent to primary care physicians. [ 18 ] Therefore, primary care and family physicians play a vital role in improving transition care resulting in reduced hospital readmissions,[ 26 32 ] and their turnover can affect readmission rates. [ 33 ] We conducted the first study analyzing avoidable readmissions among older adults in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 31 ] Another study found the odds of readmission reduced by 56% when discharge plans were sent to primary care physicians. [ 18 ] Therefore, primary care and family physicians play a vital role in improving transition care resulting in reduced hospital readmissions,[ 26 32 ] and their turnover can affect readmission rates. [ 33 ] We conducted the first study analyzing avoidable readmissions among older adults in India.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] As liaisons between the various healthcare practitioners involved in patient care, primary care physicians can play a vital role in post-discharge care and reduce hospital readmissions by providing continuing care. [ 26 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…In an aging population, increasing numbers of individuals experience extended periods with frailty and multimorbidity toward the end of life (Tunnard et al, 2021). Subacute settings provide specialized levels of care to patients with longer periods of frailty, deterioration, and complex conditions who do not require the intensity of care provided in acute settings (Menzies & Hanger, 2011;Reyes-Ortiz et al, 2015;Robert et al, 2021;Sinn et al, 2016;Tunnard et al, 2021;Walker et al, 2015). Subacute care aims to provide continuity of care for patients as an intermediate step between acute care and home (Robert et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Subacute settings provide specialized levels of care to patients with longer periods of frailty, deterioration, and complex conditions who do not require the intensity of care provided in acute settings (Menzies & Hanger, 2011;Reyes-Ortiz et al, 2015;Robert et al, 2021;Sinn et al, 2016;Tunnard et al, 2021;Walker et al, 2015). Subacute care aims to provide continuity of care for patients as an intermediate step between acute care and home (Robert et al, 2021). However, while interventions exist to improve the hospital-to-home transition, these have generally focused on acute care.…”
Section: Introductionmentioning
confidence: 99%
“…Individu dalam kelompok bothstudy dikecualikan jika mereka dibawah 60 tahun, kehilangan informasi usia dan jenis kelamin, dan tidak memenuhi syarat untuk didanai oleh publik Ontario Health Insurance Plan (OHIP). ( Robert, H. Sun, Sinden, Spruin, & T. Hsu, 2020) Melalui wawancara yang saya lakukan terhadap nenek saya yaitu nikmah ammar, yang bisa di panggil ibu nikmah, sekarang berusia 75 tahun kelahiran 16 april 1945 dan pendidikan terakhir SMA, bertempat tinggal di Situbondo bersama kakak kandung ibu saya (paman saya). Dari informasi yang saya dapatkan dari nenek saya mengenai penyakitnya, nenek saya menderita penyakit asma yang mana sering sekali kambuh apa bila melakukan kegiatan-kegiatan yang berat.…”
unclassified